Pengaruh Penggunaan Media Flash Card terhadap Penguasaan Kosakata Bahasa Arab Siswa Madrasah Ibtidaiyah - Nofiadi, Moh. Sholeh; Taubah, Miftachul; Syarifuddin, Syarifuddin (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to determine the effect of flash cards on the mastery of Arabic vocabulary among fifth-grade students at MI Raudlatul Mutaallimin Bangkalan. Using a quantitative approach with a one-group pretest-posttest pre-experimental design, data were collected through observation, interviews, and tests. Data sources include teachers and students (primary data) and previous scores (secondary data). The population in this study consists of 26 students. Purposive sampling was chosen to determine the sample. Data analysis techniques used in this study include the Normality Test and the Paired Sample t-test. The study results showed a significant increase, with the average student score rising from 55.88 (pre-test) to 87.12 (post-test). The Paired Sample t-test yielded a significance value of 0.000 (< 0.05), indicating a significant difference before and after using the media. Thus, flashcards have proven effective in improving Arabic vocabulary mastery and are recommended as an engaging and enjoyable learning medium, particularly at the Madrasah Ibtidaiyah level.